Human experience is not a line item - Jason Wolf (The Beryl Institute, 2022)
Our humanity is fundamentally defined in context with others, in our relationships that reinforce or bend who we are, in the interactions through which we wither or grow. It is these interactions that rest squarely at the heart of the healthcare experience. For over a decade, we have defined experience in The Beryl Institute community as the sum of all interactions, shaped by an organization's culture that influence patient perceptions across the continuum of care. The power of the simple, yet significant nature of these words reinforces the idea that experience happens primarily at the touch point between people. These experiences, ultimately, are framed by the kinds of organizations we build, cultures we foster, behaviors and choices we encourage and expect. The humanity we build into our healthcare system is the basis for every experience one has. The conduit for these experiences is the healthcare workforce itself. The context for experience happens in the communities that healthcare serves. These ideas are not simply an idealized state but also have tangible and measurable impacts on healthcare itself. This special issue helps us to see some of the implications and actions of the healthcare workforce experience on our capacity to deliver the best in care overall. Experience is not a line item - for an investment in experience efforts creates a culture shift that has direct bearing on the quality outcomes realized, the patient and family loyalty sought, the community reputation desired and the vibrant workforce that healthcare leaders strive to ensure every day. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens